Pemberdayaan Ekonomi Desa Sokkolia Melalui Pelatihan Pembuatan Sabun Sebagai Produk Usaha Rumahan - Yuni Rahmah; Rosnia, Rosnia; Jasri, Jasri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Sokkolia Village is one of the areas with considerable human resource potential but still faces challenges in terms of the economic independence of its residents. The majority of the community, especially housewives, lack entrepreneurial skills that can be utilized to support family income. Observing this condition, this community service activity was carried out with the aim of empowering the local economy through training in liquid soap production as a home-based business product that is both economically valuable and environmentally friendly. The method used in this activity consisted of three main stages: (1) a workshop on business opportunities and the benefits of liquid soap for health and the environment; (2) technical training on the production of liquid soap, including material selection, mixing process, packaging, and product trials; and (3) initial marketing assistance through local promotion strategies and social media. This activity involved active community participation, particularly among women’s groups, using a participatory approach and hands-on practice. The main results of the activity showed a significant increase in participants' knowledge and skills related to the production process of liquid soap. Some participants have successfully produced liquid soap independently and have begun selling the products within their local community. This initiative has opened up new business opportunities, strengthened family economies, and fostered a local entrepreneurial spirit.